The impact of the application of total quality management on the performance of banks - Maher Ali Ahmed; Nasreen Mustafa Sajid (Peerian Journals Publishing, 2023)
The purpose of this study is to assess the impact of banks' application of integrated quality principles on their performance effectiveness by focusing on improving customer and employee needs and improving bank operations. The results show that applying these principles leads to an improvement in institutional performance by more than 70%, which contributes to enhancing the competitiveness of the banking industry and achieving outstanding performance goals. The research is based on a descriptive approach and the use of customer and employee satisfaction questionnaires and agency performance indicators, in addition to statistical tools to analyze data and conclude the importance of applying integrated quality principles in improving organizational performance.
Keywords: Total Quality Management; Financial Banks; Quality of Service